Catastrophic impact of 1947 partition of India on people's health - Tanveer, Tuba; Mathur, Nixon; Sarwal, Rakesh (Journal of family medicine and primary care, 2024)
ABSTRACT Introduction: The partition of India on the dissolution of British Raj into two dominions is known to have been violent, polarizing and caused large-scale loss of life (about two million) and an unprecedented migration of 14 million people between the two dominions, India and Pakistan. It is not known how well the then scientific community covered this man-made disaster, and the response of the international community with aid. Methodology: A systematic review was conducted using different electronic databases of PubMed, Econlit, United Nations resolutions, Government of India websites, and Google Scholar for the period January 1947 to December 1951 on the impact of the partition of the Indian sub-continent, and to identify the international response toward this humanitarian crisis. Result: We could locate only twenty-four publications. Partition not only caused monumental humanitarian suffering, but also contributed to food deficits, adverse impact on trade and industries, national income and harmed public health. In contrast, no significant attention was expressed by the international scientific community or the United Nations, or aid provided during this catastrophic event. Conclusion: The review demonstrates the apathy by the contemporary international scientific research community on the social as well as economic damage caused by the partition of India. We suggest that the international scientific and research community should play the role of vigilante and fact finder to unearth the facets of mass human tragedy and its long-term consequences so that global consciousness is awakened, and help and aid flows when it is most needed.